Basic Tenth Grade Students’ Arguments about Socio-Genetic Issues in Biology as Related to Reasoning Patterns - Al-Jrrah, Zead; Khataibeh , Abdollah; Bni Khalaf, Mahmoud (Jordan Journal of Educational Sciences, 2013)
This study aimed at exploring the quality of arguments and reasoning patterns of students in the Basic tenth grade in Jordan on issues of cloning, genetic engineering, endogamy, and premarital genetic screening. To achieve the objectives of the study, the researcher used a qualitative method. The study sample consisted of 30 students selected according to the purposeful sampling, maximum variation sampling type. The researcher used a semi-structured interview to collect data. The data were analyzed inductively using Toulmin Model of the arguments to determine the level of the arguments of participating students. Further, the patterns of reasoning (rational, emotional and intuitive) were used as a framework for determining the kind of reasoning used by the participants on the above mentioned genetic-social issues. The results of the analysis of the findings of the study showed that the majority of the students were at the second level of the arguments, where they recorded 72% of all cases. Then came the third level with 14%, followed by the first level with 12%, and the fourth level just above 2% only. Data analysis has also showed control of the participating students on the use of intuitive and emotional reasoning (66% and 50% in succession). Thirty one of the students participating in the study have used the rational reasoning. It was clear from the results of the study that the students were able to present arguments on socio-scientific issues, but not up to the prospective educational level.